Jump test on a force platform for applicants to a sport science degree - Lara, A.; Abian, J.; Alegre, L. M.; Jiminez, L.; Aguado, X. (Journal of Human Movement Studies, 2006)
The purposes of this study were, firstly, to obtain descriptive data with a force platform on the push-off phase and height of a counter-movement Jump (CMJ), in a sample of applicants to a faculty of Sports Science, and secondly, to compare three different methods of measuring jump height. The CMJs of 161 men (weight, 70.37±8.33kg; age, 19.4±2.9 years) and 79 women (58.43±8.78kg; age 18.9±2.2 years) who were applicants to a Spanish Faculty of Sports Science were analysed. Jump performance was tested on a portable piezoelectric force platform (Quattro Jump, Kistler). The variables studied were: height of rise of centre of gravity (h), peak vertical force (PF), force at the transition from eccentric to concentric phase, peak power (PP), and average power. Jump height was assessed using three different ways: from the flight time, from the impulse-momentum method, and from the double Integration (work-energy) method (Linthorne, 2001). The results were äs follows: h was 34.6±4.3cm (men) and 25.7±4.7cm (women); PF was 2.43+0.26 body weight (BW) (men) and 2.28±0.26 BW (women), and PP was 50.1±5.2W/kg (men) and 40.5±5.4W/kg (women). The results of the present study show a lesser jump performance than Spanish physical education students from previous works, which is probably related to the increase in the number of faculties of Sports Science in recent years in Spain. Although the differences in jump height between the three methods were small, they were statistically significant (p<0.001). If portable force platforms become widely utilised, CMJ heights obtained on contact mats will have to be adjusted to about 2cm less for comparison purposes.